(2x/5)-x=(x/15)-(10/3)

Simple and best practice solution for (2x/5)-x=(x/15)-(10/3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x/5)-x=(x/15)-(10/3) equation:


x in (-oo:+oo)

(2*x)/5-x = x/15-(10/3) // - x/15-(10/3)

(2*x)/5-x-(x/15)+10/3 = 0

10/3-2/3*x = 0 // - 10/3

-2/3*x = -10/3 // : -2/3

x = -10/3/(-2/3)

x = 5

x = 5

See similar equations:

| (X/2)-(2/3x)=(2/3) | | 20+2y-6=11y-10-5y | | 3y-6+y+26=5y+20-3y | | -3x-2y=-14 | | 24/3+5X4-21 | | -2x=4x-42 | | ((k-7)/5)+2=((k+8)/10) | | 24/3+5*4-21 | | v^2+4v-45= | | 1/8+a/32 | | 33.6x=70-1.4x | | 1/2(5t-7)=9/2t-(t+7/4) | | .0795t^2-.884t+1.798=0 | | -0.6x+0.5=0.1 | | 12=x+7.2 | | (2x-5)/(x-6)=0 | | x-8.8=-5.6 | | 7x+2x=x-6 | | x/4+1/2 | | 2(-8-4x)=-56 | | 3x+4y=560 | | 2(y-9)=-5y-4 | | 12.00-2x=10.00 | | 9x-2=7x | | a-2.9=-3.6 | | 28-12x/4=-8x-12/10 | | 53/5+4/5 | | 1-2.9=-3.6 | | 6.2x-4+x-1.2= | | 17-44=3(x-1)-6 | | 7j+11=14 | | 2x=4x-14.2 |

Equations solver categories